Detection of HBsAg and serotypes in blood plasma of HBV-positive individuals in Mongolia - Dolgion, Damdinbazar; Bolortuya, Byambajav; Otsuka, Toshiaki; Tserendejid, Magvansuren; Erdenebayar, Namjil; Oyunsuren, Tsendsuren; Gantulga, Davaakhuu (Proceedings of the Institute of Biology, 2023)
Mongolia has the highest liver cancer incidence in the world, primarily attributed to hepatitis virus infections and the prevalence of liver diseases. The predominant focus in existing studies involved the detection of virus infections, and immunization against HBV, with HBsAg serving as a primary marker. In this study, blood donation samples were evaluated, which were positive for HBV and negative for HCV, HAV, HIV, and syphilis by ELISA test at the National Center for Transfusion Medicine (NCTM) of Mongolia. Furthermore, titer determination was performed by reverse passive hemagglutination (PHA) assay, and the antigen serotype was identified on an isolated HBsAg. Our result showed that, among 83 HBV-positive blood plasmas, 10 exhibited a high HBsAg titer, and the serotypes ayr and ayw were identified. The samples were categorized into groups A and B, and to analyze HBsAg reliability, the prototype models were assembled using HBsAg isolated from the high antigen yield group (A). As a result, the prototype models were stable in 3 months, but the sensitivity and specificity of the antigen were weaker compared to its standard. Хепатитийн B вирус (HBV)-ийн халдвартай хүний цуснаас HBsAg ялган, серотипийг тодорхойлсон дүн Хураангуй. Монгол улсын хүн амын дундах хепатитийн вирусийн халдвар болон вирусийн шалтгаант элэгний өвчлөлийн тохиолдол дэлхийд тэргүүлэх байранд байдаг. Олон улсад хепатитийн B вирус (HBV)-ийн оношилгоо болон дархлаажуулалтын судалгаанд гадаргуугийн эсрэгтөрөгч (HBsAg)-ийг өргөнөөр ашигладаг. Бид манай Цус сэлбэлт судлалын үндэсний төв (ЦССҮТ)-д цуглуулсан HBV-ийн халдвартай 83 донорын цусны ийлдэс дэх HBsAg-ийн илэрцийг тогтоон, эсрэгтөрөгчийн илэрц өндөр 10 дээжийг А болон Б бүлэгт ангилан HBsAg-ийг ялгаж, тус бүрд ayr болон ayw серотипүүдийг тодорхойлсон. Улмаар эсрэгтөрөгчийн агууламж өндөр А бүлгээс ялган авсан бөмбөлөг ба утаслаг эсрэгтөрөгчийг ашиглан прототип загварыг гарган авч шинж чанарыг тодорхойлоход тэдгээрийн тогтвортой байдал сайн хэдий ч мэдрэг болон өвөрмөц чанар нь стандарт эсрэгтөрөгчтэй харьцуулахад сул болохыг тогтоов. Энэ нь бидний судалгаагаар ayr болон ayw серотип бүхий эсрэгтөрөгч илэрсэнтэй хамааралтай байх боломжтой. Түлхүүр үгс: серотип, эсрэгбиеийн таньц, прототип загвар